Ankle and Foot Injuries in the Young Athlete - Chauvin, Nancy A.; Jaimes, Camilo; Khwaja, Asef (Seminars in Musculoskeletal Radiology, 2018)
Injuries to the ankle and foot are common in the young athlete, especially with increasing participation and high levels of competitiveness in youth sports programs. Knowledge of the normal development of the foot and ankle is crucial to understand age-specific injury patterns because acute or chronic/repetitive stress to the developing skeleton results in injuries that differ from those seen in adults. Congenital abnormalities may also predispose children to increased risk of injury and pain. Radiologists must be aware of these distinctions to diagnose and classify injuries correctly for optimum treatment. We describe common and unique foot and ankle injuries in the young athlete. Throughout the article we focus not only on imaging findings but also on the mechanism of injury.
Keywords: ankle injuries; foot trauma; children; pediatric athlete; sports injuries